Wymagalność roszczenia o wynagrodzenie wykonawcy robót budowlanych - Zagrobelny, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Determining the maturity of a claim for building contractor’s remuneration seems to be a crucial theoretical issue. It is of considerable practical importance, too. The basic difficulty in determinig the moment at which it becomes due and payable is connected with evaluation of the legal nature of acceptance of a building. In the present paper it has been assumed that a lack of cooperation on the part of an investor upon such acceptance does not exclude the possibility to acknowledge that the contractor has fulfilled their performance, and thus it creates a basis for pursuing a claim for remuneration.
Keywords: claim; claim for building; contractors remuneration; maturity of a claim